Prevalence and trend of major transfusion-transmissible infections among blood donors in Western China, 2005 through 2010. - Yan Song; Ying Bian; Max Petzold; Carolina Oi Lam Ung (PLoS ONE)
Background The prevalence of transfusion-transmissible infections (TTIs) in blood donations is important for evaluating blood safety and potential risks to the population. This study investigated the prevalence of TTIs among blood donors in Western China and suggested measures for policy-makers. Methods The screening results of 66,311 donations between 2005 and 2010 from a central blood center in Western China were analyzed. The prevalence of hepatitis B virus (HBV), hepatitis C virus (HCV), human immunodeficiency virus (HIV), and syphilis infections were expressed in percentages for the entire study group as well as groups by demographic characteristics and donation frequency, with differences analyzed using Fisher's exact or Chi-square test. Logistic regression was performed to identify the influencing factors of the detected results. Results 1,769 (2.67%, 95% CI 2.55-2.79%) of the donated blood had serological evidence of infection with at least one pathogen and 44 (0.07%, 95% CI 0.05-0.09%) showed evidence of multiple infections. The seroprevalence of HBV, HCV, HIV, and syphilis infections was 0.87% (95% CI 0.80-0.94%), 0.86% (95% CI 0.79-0.93%), 0.31% (95% CI 0.26-0.35%), and 0.70% (95% CI 0.64-0.76%) respectively. Trend analysis for the prevalence of TTIs showed a significant increase from 2.44% to 3.71% (χ2 = 100.72, p = 0.00) over this 6-year period. The positive rates for TTIs varied along demographic lines. The top three risk factors in test-positive donors were identified as age, education level and donation frequency. The older age group and lower educated group were linked to a higher prevalence of TTIs. A decreasing prevalence was associated with an increasing frequency of blood donations (χ2 = 562.78, p = 0.00). Conclusions Hepatitis B and C were found most, and often in conjunction with syphilis. These were the primary threats to blood safety. The high positivity rate and the increasing prevalence of TTIs among blood donors in Western China call for further actions.